INTERCULTURAL DIALOGUE IN ASIAN COUNTRIES: CHALLENGES AND PROSPECTS (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This paper examines the importance of intercultural dialogue in Asian countries, its role in the modern world of globalization, as well as the challenges and prospects that different peoples face in the process of interaction. The cultural, social and economic aspects of this dialogue, as well as examples of successful cooperation and conflicts are discussed.